Pozyskanie tajnego współpracownika przez służby kontrwywiadowcze na podstawie materiałów obciążających — rozważania o sensie instytucji - Herbowski, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The basic task of state authority is to ensure the security of state structures and its citizens. This can be achieved by legal solutions allowing the counterintelligence services to recruit secret collaborators based on possessed incriminating materials. This instrument meets the expectations of Polish counterintelligence services, however, the lack of resolution of many issues puts into question the possibility of its application in practice.
Keywords: tajny współpracownik; materiały obciążające; kontrwywiad; bezpieczeństwo państwa